Financial Distress: Profitability Ratios and Liquidity Ratios, with Financial Statement Fraud as Moderating - Fajar Wisnu; Dwi Puji Astuti (Economic Education Analysis Journal, 2023)
The purpose of this study is to examine the effect of profitability ratios and liquidity ratios on financial distress, with fraudulent financial statements as a moderating variable. This research is quantitative research. The population of this study are agricultural companies listed on the Indonesia Stock Exchange for the period 2018-2021. The data collection method used purposive sampling technique and obtained a sample of 19 companies with 76 units of analysis. The secondary data used is the annual financial report which is downloaded through the IDX's official website. Analysis of research data using descriptive statistical analysis and Structural Equation Modeling-Partial Least Square (SEM-PLS) with the application tool WarpPLS 8.0. The results show that partially the profitability ratios have no effect on financial distress, liquidity ratios have a positive effect on financial distress, financial statement fraud has a negative effect on financial distress, fraud is not able to moderate the effect of profitability ratios on financial distress, and fraud is able to moderate the effect of liquidity ratios financial distress.